Cain, Louis P. Chicago before the Fire: An Economic History - Glaeser, Edward L. (Journal of Economic Literature, 2026)
Edward L Glaeser of Harvard University reviews “Chicago before the Fire: An Economic History” by Louis P. Cain The Econlit abstract of this book begins: “Examines the economic and business history of Chicago before the Great Fire of 1870, focusing on how the city's early growth and development determined its rise as the Midwest's dominant city.”